Multiaxial tension/compression asymmetry of Ti/TiN nano laminates: MD investigation. (15th August 2017) - Yang, Wei; Ayoub, Georges; Salehinia, Iman; Mansoor, Bilal; Zbib, Hussein
Abstract: Metal-ceramic multilayers have been reported to show high strength, measurable plasticity, and a high strain-hardening rate when the crystallographic layers are a few nanometers thick. In this work, large-scale molecular dynamics simulations are carried out in order to understand the deformation mechanisms of the Ti/TiN multilayer subjected to multiaxial loading. The yield behavior of the Ti/TiN multilayer is thoroughly explored by constructing the yield surface in the interface plane. The strong dependency of the yielding stresses on the loading direction highlights the anisotropic behavior of the structure. The Ti/TiN multilayer structure shows high strength and ductility under uniform compression loading. However, low strength and ductility are observed under tensile loading, which favors crack initiation and propagation. Unlike typical metal stress-strain curves, metal/ceramic multilayers show two main yield points. Furthermore, the Ti/TiN multilayer structure shows three distinctive peak points for compressive loading normal and parallel to the interface. Different slip planes are activated depending on loading directions. Two main mechanisms are found to control the plasticity of the Ti/TiN multilayer: (1) interface strengthening, in which, when the metal-ceramic multilayers are under compressive loading, the interface acts as a barrier and induces repulsive forces against the slip transmission from the Ti layer into the TiN layer; (2) interface softening, in which, when applying tensile loading on the metal-ceramic multilayer structure, the interfacial misfit dislocations act as sources for the emission of dislocations into the TiN layer or promote slip transmission from the Ti to the TiN layer. Graphical abstract: Image 1